2017
DOI: 10.1152/ajpregu.00168.2017
|View full text |Cite
|
Sign up to set email alerts
|

Functional and neurochemical characterization of angiotensin type 1A receptor-expressing neurons in the nucleus of the solitary tract of the mouse

Abstract: Angiotensin II acts via two main receptors within the central nervous system, with the type 1A receptor (ATR) most widely expressed in adult neurons. Activation of the ATR in the nucleus of the solitary tract (NTS), the principal nucleus receiving central synapses of viscerosensory afferents, modulates cardiovascular reflexes. Expression of the ATR occurs in high density within the NTS of most mammals, including humans, but the fundamental electrophysiological and neurochemical characteristics of the ATR-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…As some neurons received more than one visceral sensory input, we examined nine direct ST inputs onto seven second-order neurons (mean series resistance ϭ 14.35 Ϯ 3.18 M⍀). Previously, we have demonstrated that 2 M ANG II induces a 3-mV depolarization in AT 1A R-expressing NTS neurons (15). In the present study, ANG II application resulted in the development of an inward current, Ϫ6 Ϯ 1 pA (range from Ϫ1 to Ϫ10 pA) in each second-order neuron tested in 2 mM [Ca 2ϩ ] o (n ϭ 7, P Ͻ 0.05 Student's paired t-test).…”
Section: St Input Converges At Individual At 1a R-expressing Neuronssupporting
confidence: 62%
See 3 more Smart Citations
“…As some neurons received more than one visceral sensory input, we examined nine direct ST inputs onto seven second-order neurons (mean series resistance ϭ 14.35 Ϯ 3.18 M⍀). Previously, we have demonstrated that 2 M ANG II induces a 3-mV depolarization in AT 1A R-expressing NTS neurons (15). In the present study, ANG II application resulted in the development of an inward current, Ϫ6 Ϯ 1 pA (range from Ϫ1 to Ϫ10 pA) in each second-order neuron tested in 2 mM [Ca 2ϩ ] o (n ϭ 7, P Ͻ 0.05 Student's paired t-test).…”
Section: St Input Converges At Individual At 1a R-expressing Neuronssupporting
confidence: 62%
“…Two-thirds of AT 1A R-expressing neurons receive direct visceral sensory inputs placing ANG II in a position to directly influence reception of visceral sensory information. Based on previous data (11,15), ANG II sensitizes NTS neurons to reception of sensory afferent information. Key to this conclusion, which is derived from our use of an ST recruitment protocol, is that ST-EPSCs which display high variability in synaptic latency involve interneurons between the stimulated visceral afferent and the recorded neuron.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, CCK, oxytocin, ghrelin, serotonin, and opioids all control NTS neuronal activity indirectly through presynaptic modulation of glutamate release (2, 6, 15-17, 36, 43, 45, 69, 90). Interestingly, angiotensin II was also recently shown to have postsynaptic actions on NTS neurons (13), and oxytocin has postsynaptic actions in a subpopulation of NTS neurons (43,69).…”
Section: R45mentioning
confidence: 99%